Efficacy of acupuncture in patients with mild Alzheimer’s disease and its impact on gut microbiota: Study protocol for a randomized sham-controlled trial - Kong, Xiehe; Ma, Zhao; Tang, Ran; Wang, Xuejun; Wei, Kai; Yang, Guang; Yang, Yanting; Zhao, Yue; Zhang, Dan; Xie, Chen; Wang, Gang; Ma, Xiaopeng (Frontiers in Medicine, 2023)
Introduction: Acupuncture is used as an adjuvant therapy for Alzheimer’s disease (AD), but available evidence for efficacy is limited so far. Growing studies suggest that resident gut microbiota contributes to the development and progression of AD. Meanwhile, acupuncture is reported to treat gastrointestinal and neurodegenerative disorders via the gut-brain axis. Therefore, our aim is to confirm the adjunctive therapeutic effects of acupuncture for AD, and explore the relationship between clinical efficacy and shifts of gut microbiota. Methods and Analysis: This is a randomized, participant-masked, sham-controlled trial. One hundred and sixty participants with mild AD will be randomly assigned (1:1) to either active acupuncture or non-penetrating sham acupuncture (3 times weekly for 14 weeks) added to donepezil treatment (5 mg per day for 28 weeks). The primary efficacy outcome is the change from baseline to week 28 in the Alzheimer’s disease Assessment Scale (ADAS-cog12). Secondary efficacy outcomes include other assessments of the Mini-Mental State Examination (MMSE), the Alzheimer’s disease Cooperative Study-Activities of Daily Living (ADCS-ADL) and Neuropsychiatric Inventory (NPI). Gut microbiota will be measured using 16S rRNA tag sequencing. Discussion: This rigorous trial will provide high-quality evidence on the efficacy of acupuncture as adjunctive treatment for mild AD, and identify the possible mechanisms of acupuncture from gut microbiota. Trial registration: ClinicalTrials.gov, NCT05078944. Registered 15 October 2021, https://clinicaltrials.gov/ct2/show/NCT05078944